A prospective, multi-centre, observational study to examine kidney disease progression in adults with chronic kidney disease - CKDOD - Study design and preliminary results - Shah, B.; Kirpalani, A.; Sunder, S.; Gupta, A.; Khanna, U.; Chafekar, D.; Tan, L.P.; Sirivongs, D.; Pahari, D.; Nath, G.; Ikizler, T.A. (2015)
Background: The objective of this article is to describe the organisation of an international, clinical registry, the Chronic Kidney Disease Observational Database (CKDOD), the processes of enrolling patients and entering data and preliminary results to date. Design: The Chronic Kidney Disease Observational Database (CKDOD) is designed to assess the association between different factors with a known influence on chronic kidney disease (CKD) progression as well as treatment strategies such as dietary modifications, blood pressure control and pharmacological interventions in Asian countries (India, China, Malaysia and Thailand). The only inclusion criterion is the presence of CKD stage 2 or higher as defined by the KDIGO guidelines. Demographic and clinical information are collected by a standardised electronic questionnaire, available in English and Chinese. The data are transferred to the CKDOD database either by e-mail or via web access. All data are checked for consistency and missing values. Collection of data started in September 2011 and by April 2015, data on 1323 individual patients had been submitted. The mean age at inclusion was 57 +/- 14 years, 67 % were male and 36 % were diabetic. The baseline estimated glomerular filtration rate was 26 ml/min/1.73 m(2). Of all enrolled patients, 324 (24 %) received ketoanalogue supplementation during at least one recorded visit. Discussion: The CKDOD is a very large and comprehensive data repository, currently focused in subjects recruited from Asia. The database is expected to provide important long-term information on CKD progression, nutritional and metabolic derangements that accompany CKD progression and treatment strategies to ameliorate progression and complications of CKD.